Pengaruh Servicescape Terhadap Kepuasan Pelanggan (Studi Kasus Coffee Bajawa Flores Tebet) - Abiyoso Hadikusumo; Hindun Nurhidayati; Sarojini Imran (Journal of Applied Science in Tourism Destination, 2025)
This research aims to analyze the influence of servicescape on customer satisfaction (Case Study of Bajawa Flores Tebet Coffee). The method used in this research is a quantitative method. The independent variable of this research is Servicescape. Meanwhile, the dependent variable of this research is Customer Satisfaction. The sample obtained was 110 respondents using Purposive Sampling technique. This research hypothesis was tested by IBM SPSS Statistics 27 with the results of the Servicescape variable, which includes aspects of Ambient Conditions, Spatial Layout And Functionality, Signs, Symbols & Artifacts, while the dependent variable is Customer Satisfaction.  The results of these values show that visitors who visit Coffee Bajawa Tebet have their own reasons for being satisfied with Coffee Bajawa Tebet. Researchers found that the Servicescape variables consisting of Ambient Conditions, Spatial Layout And Functionality, Signs, Symbols & Artifacts, influenced Customer Satisfaction at Bajawa Tebet Coffee.